Pengaruh Sistem Penghargaan dan Kondisi Kerja terhadap Retensi Karyawan dengan Keterikatan Karyawan sebagai Variabel Mediasi - Nurdiani, Syarifah Mita; Megawati, Megawati (Syiah Kuala University Press, 2024)
The aim of this research is to analyze the influence of the Reward System and Job Condition on Employee Retention with Employee Engagement as a mediating variable in the Nursing Staff of Aceh Tamiang Regional Hospital. The sample used in this research was 133 respondents using a sampling method using the census method, and the sample used in this research was Civil Servant Nursing Staff at Aceh Tamiang Regional Hospital. The data analysis method in this research uses Statistical Program and Social Science (SPSS) to determine the influence between the variables involved. Based on the research results, it was found that the Rewards System and Job Condition have a significant effect on Employee Retention. Reward Systems and Job Condition have a significant effect on Employee Engagement. Employee Engagement has a significant effect on Employee Retention. Employee engagement mediates the effect of the Rewards System on Employee Retention. Employee engagement mediates the effect of Job Condition on Employee Retention.